Development of an integrated assessment model at provincial level: GCAM-Korea - Jeon, Seungho; Roh, Minyoung; Oh, Jaeick; Kim, Suduk (Energies, 2020)
Integrated assessment modeling at a higher spatial scale is a prerequisite for deriving region-specific implications from the model. The Global Change Assessment Model (GCAM) was chosen for GCAM-Korea, a detailed integrated assessment model (IAM) of Korea's socioeconomic and energy systems. GCAM-Korea is developed based on GCAM-USA. Data for 16 provinces have been collected from various sources. Some data have been pre-processed to fit within the specific structure of GCAM-USA data. Other types of data were newly added through new structures. The model results were validated to be compatible with historical trends. It was found that provincial energy plans or policies could be compiled in detail using the proposed model while maintaining consistency with national level modeling results. The cross-border air pollution issue in Northeast Asia could also be addressed by combining GCAM-Korea and air quality models in the future.
Keywords: Air quality models; Assessment models; Energy systems; Historical trends; Integrated assessment models; National level; Northeast Asia; Spatial scale; Energy system; GCAM-Korea; High spatial resolution analysis; Integrated assessment model